The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jhydrol.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal infrared imaging for the detection of relatively warm lacustrine groundwater discharge at the surface of freshwater bodies

Abstract: Thermal infrared (TIR) imaging has been previously applied to survey relatively large thermal footprints in coastal zones, lakes, reservoirs and rivers. In freshwater systems, the buoyancy of relatively warm groundwater during the winter months allows for the surface identification of groundwater discharge or thermal pollution using TIR imaging. However, information regarding the performance of TIR for resolving this warm groundwater upwelling is limited, particularly at fine spatial scales and variable discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Sass et al [25] detected terrestrial groundwater discharge zones with Landsat TIR data from Alberta, Canada. Arricibita et al [26], who used a TIR camera in a laboratory experiment, indicated that analysis of TIR data allows for the measurement of water surface temperature at high spatial resolution across a wide range of scales. Thus, TIR remote sensing can be applied to assess SGD and extrapolate local groundwater fluxes to a regional scale and, therefore, potentially reduce the amount of field sampling and in situ measurements required.…”
Section: Introductionmentioning
confidence: 99%
“…Sass et al [25] detected terrestrial groundwater discharge zones with Landsat TIR data from Alberta, Canada. Arricibita et al [26], who used a TIR camera in a laboratory experiment, indicated that analysis of TIR data allows for the measurement of water surface temperature at high spatial resolution across a wide range of scales. Thus, TIR remote sensing can be applied to assess SGD and extrapolate local groundwater fluxes to a regional scale and, therefore, potentially reduce the amount of field sampling and in situ measurements required.…”
Section: Introductionmentioning
confidence: 99%
“…The use of heat as a natural tracer has become a popular tool to characterize GW-SW exchange patterns due to the natural temperature differences between GW and SW and the relative ease and accuracy of temperature measurements using standard sensors. This field has evolved significantly since some of the earlier seminal works (Stonestrom and Constantz, 2003;Schmidt et al, 2006) and has embraced novel technologies such as DTS (Krause et al, 2012;Rose et al, 2013) and hand-held (Glaser et al, 2016;Marruedo Arricibita et al, 2018) or airborne infrared imagery (Lewandowski et al, 2013). The suite of methods available today allows for high-resolution assessment of temperatures in space and time for a qualitative mapping of GW-SW exchange patterns (Anibas et al, 2011;Krause et al, 2012) or a quantification of exchange fluxes (Schornberg et al, 2010;.…”
Section: Groundwater-surface Water Interactionsmentioning
confidence: 99%
“…In particular, high resolution thermal infrared (TIR) imaging has been increasingly used to quantify hydrological states through the use of temperature as a “tracer” or “signature” for (near‐) surface flow and saturation (Glaser et al., 2018). Hydrologists have used ground‐based TIR for characterizing groundwater‐surface water (GW‐SW) interactions in 2D (e.g., Briggs et al., 2013; Deitchman & Loheide, 2009; Drake et al., 2010; Hare et al., 2015; Lu et al., 2020; Pandey et al., 2013; Schuetz & Weiler, 2011), describing hydraulic processes such as surface flow velocity or mixing across the stream channel (e.g., Antonelli et al., 2017; Puleo et al., 2012) and understanding surface water energy budgets or thermal heterogeneity (e.g., Baker et al., 2019; Cardenas et al., 2014; Marruedo Arricibita et al., 2018; Tonolla et al., 2010). Ground‐based TIR has also been increasingly deployed for mapping surface saturation (e.g., Antonelli et al., 2020; Glaser et al., 2018; Glaser et al., 2020; Glaser et al., 2016; Pfister et al., 2010; Figures 1a and 1b).…”
Section: Current State Of the Artmentioning
confidence: 99%